Experience of rural families when having a father/husband with prostate cancer - Caroline Vieira Mathias; Margrid Beuter; Nara Marilene Oliveira Girardon-Perlini (Rev Rene)
Objective: To report the experience of rural families when having a father/husband with prostate cancer illness. Methods: qualitative research, conducted at the residence of four rural families with nine subjects. A semi-structured interview was used, and thematic categories were established by the data analysis. Results: men with cancer were between 66 and 68 years old, knowing the diagnosis at least four years ago. Respondents family members were wives or children, aged between 30 and 69 years old. Families worked on agriculture and livestock. The nominated category A prostate cancer in our life is formed by the sub-categories: discovery of the diagnosis; family support; changes resulting from illness and difficulties faced during treatment. Conclusion: the rural family experience is full of constant division of tasks between the care for the father/husband and work activities, changes in marital life, sadness, distress and hopes about an uncertain future.